Biomimicry – Core Stages, Design Process, and Gaps - Toong Foo, Chin; Omar, Badrul; Jalil, Azlis-Sani (International Journal of Engineering and Technology, 2019)
Nature is a world-scale R&D in a laboratory called the universe. Some of the best inventions and innovations are actually built based on natureâ€™s design. But in order to wield the power of natureâ€™s design, one must first learn about the three core stages of biomimicry: Search, Abstract, and Transfer. One must also know the steps of designing with biomimicry, either problem-driven or solution-based design process. Since Theory of Inventive Principles (TRIZ) is known as the most promising tool to bridge the biology-engineering gap, this paper presented both problem-driven and solution based design process with TRIZ cycle. There had been many biomimicry tools emerging since 1987, but tuning and refinements are still required. The biology-engineering gap is still far from being bridged. This paper presented some of the ideas of potential approaches in bridging the biology-engineering gap; TRIZ, Function-Behaviour-Structure (FBS) modelling, and pattern language.Â Â